Moderne Umgestaltungen im Grundriss iranischer Städte (1) - Scharlau, Kurt (ERDKUNDE, 1961)
The increasing amount of modernisation of Persian towns becomes geographically particularly impressive by the thorough re-shaping, i. e. modernising of their ground plans. This process was initiated when, after his accession to the throne in 1926, Reza Shah Pahlewi began to build a network of strategic roads. These, which like the old caravan trails lead right through the city centres, necessitated extensive through cuts which were carried out regard less of boundaries of properties or plots. As a result the old ground plans were greatly changed and have since been characterised by broad through roads intermittently widening to round squares (example: Gurgan). New towns founded since Reza Shah’s accession and towns rebuilt after destruction by earthquakes (Bojnurd, Quchan) were on the other hand laid out on a rational grid pattern. The changes are most impressive in the groundplans of the large cities for which Meshed (Mashad) is an excellent example. This city, which is frequently visited by Europeans, has been described in detail by Stratil-Sauer so that the changes which have taken place can be followed up to the present (cf. city plan). The modernisation of Meshed was pushed through successfully by Reza Shah against considerable opposition from the Shiite clergy. This reshaping and extension of the city which he initiated is still being continued. Meshed is today the leading pilgrimage place of Persia, the Mecca of the Shiahs and is now visited by about 200000 pilgrims annually. The modernisation of the city has also had its consequences on the entire life of the inhabitants, and the Shiite clergy, has largely adapted itself to this development. On the other hand the respective development of Qom, the seat of the supreme Shiite clergy, has so far been less progressive. In contrast to these two cities the capital Teheran, dealt with in a monograph by Bobek, shows barely any national Persian characteristics. Here the old walls and gates were also sacrificed to the demands of modern traffic. The quickly growing city with its 1.5 million inhabitants, is spreading increasingly over an irregularly parcelled building area (cf. city plan), and shows in its buildings a disharmonic juxtaposition of various styles imported from many different countries. In the further environs of Teheran the consequences of rural depopulation are particularly striking but they are also noticeable around smaller towns. The increasing spread of modern traffic has also changed the entire settlement structure of the country, a tangible indication of this being the ruins of disused caravanserais. In summarising this modernisation of Persian towns which was illustrated by some examples, the question arises whether in the last instance this is an expression of a de-orientalisation of the way of life as a whole. This is certainly not the case. It appears rather that there are in Persia spiritual forces at work which successfully aim to preserve the indigenous cultural heritage against threatened alienation.